Evaluation of knowledge and application towards ergonomic principles among undergraduate dental students (Research, Society and Development, 2021)
This study evaluated the knowledge and application of ergonomic principles as well as manifestation of pain by dental students at the Federal University of Maranhão. Forty-four students answered a questionnaire on ergonomic principles. Photographs of the clinical rounds were performed to evaluate the postures adopted, without the students knowing the moment of photographic registration, avoiding that they modified their posture. The relationship between theoretical knowledge and the applicability of ergonomics in dental setting was evaluated. Data were analyzed using descriptive statistics. The Chi-square test analyzed the distribution of categorical variables among the evaluation instruments (α = 5%). Most of the participants adopted a satisfactory posture and presented knowledge about ergonomic postures, however, one can observe the poor positioning of the eyes and spine. 75% of the patients experienced pain in the body, being the spine (61.4%) and neck (40.9%) the most affected sites. The sample evaluated had good knowledge on ergonomic principles, but these were not adopted entirety, which may have led to the onset of pain.